No limite do silêncio : um estudo sobre o abuso sexual contra crianças e adolescentes no município de Muniz Freire, ES - Morais, Viviane Lopes de (2009)
This work aims to study the family sexuak abuse in children and adolescent in the city of Muniz Freire , state of Espírito Santo. An exploratory qualitative research was made. The data of the qualitative analysis has been gottenthrough a nos Serviço de Enfrentamento and Conselho Tutelat, through stories of children and adolescents, victims of family sexual abuse; both important entrance doors of the case of sexual abuse. In this way, the theorical contribuition of different authors in essencial to understand the sexual abuse experience with children.